2008
DOI: 10.1111/j.1365-2745.2007.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and wood density predict tree mortality in Amazon forests

Abstract: Summary Tree mortality is an important process in forest ecology. We explored the extent to which tropical tree death is a predictable outcome of taxon and individual level properties by means of mixed‐species logistic regression, for trees ≥ 10 cm in diameter. We worked in two lowland forest regions with markedly different floristic composition and dynamic regimes – the high wood density, low‐mortality northeastern (NE) Amazon (in eastern Venezuela), and the low wood density, high‐mortality northwestern (NW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
161
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(179 citation statements)
references
References 50 publications
14
161
1
3
Order By: Relevance
“…The NE Amazonian forests in our study are towards the higher end of the range, whereas the NW forests are close to the average for terra firma forests. Although the stem mortality rate (number of dead trees) in NE Amazonia was low (Chao et al, 2008b), there was high mortality mass input (amount of dead mass) ( Table 2). This pattern suggests that big trees died in the NE forests (see also Chao et al, 2008b) and necromass is closely related to mass-mortality rates rather than stemmortality rates.…”
Section: Stocks and Determinants Of Measured Cwd Across Terra Firma Amentioning
confidence: 99%
See 1 more Smart Citation
“…The NE Amazonian forests in our study are towards the higher end of the range, whereas the NW forests are close to the average for terra firma forests. Although the stem mortality rate (number of dead trees) in NE Amazonia was low (Chao et al, 2008b), there was high mortality mass input (amount of dead mass) ( Table 2). This pattern suggests that big trees died in the NE forests (see also Chao et al, 2008b) and necromass is closely related to mass-mortality rates rather than stemmortality rates.…”
Section: Stocks and Determinants Of Measured Cwd Across Terra Firma Amentioning
confidence: 99%
“…Although the stem mortality rate (number of dead trees) in NE Amazonia was low (Chao et al, 2008b), there was high mortality mass input (amount of dead mass) ( Table 2). This pattern suggests that big trees died in the NE forests (see also Chao et al, 2008b) and necromass is closely related to mass-mortality rates rather than stemmortality rates. When using a larger sample of published terra firma studies, we find positive relationships between necromass and biomass (AGB coarse ), mortality mass input (I recent ), and plotlevel average living wood density (ρ BA j ).…”
Section: Stocks and Determinants Of Measured Cwd Across Terra Firma Amentioning
confidence: 99%
“…Several authors have reported that stems grow at below-average rates in the years or months prior to mortality (Wyckoff and Clark, 2002;Bigler and Bugmann, 2003;Chao et al, 2008;Vasconcelos et al, 2012). Similarly, unobserved recruits that die may have lower than average taxon-level wood density, as this has been shown to be a predictor of mortality (Chao et al, 2008;Kraft et al, 2010). Both these factors may cause our assumed growth in CIC 2 to be too high, although we deal with this by using median growth estimates for the unobserved growth of known stems that die and of unobserved recruits, as explained above.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed the diameter growth rate of unobserved recruits to be the median rate for dicotyledonous stems in the 10-19.9 cm size class. We chose this as a lower estimate than the size class mean growth rate or the mean growth rate of recruits, since stems are reported to have reduced growth in the months immediately prior to mortality (Chao et al, 2008). We assigned stem wood density as the same as the plot mean in that census.…”
Section: Treatment Of Differing Census Interval Lengthmentioning
confidence: 99%
“…The physical and mechanical properties of wood can affect the growth and development of woody plants by determining water conduction and mechanical support [46], and are closely linked with the morphological structure of individual [7], life-history strategy [8], resource competition [9], community dynamics [10] and the terrestrial ecosystem function of trees [11,12]. Therefore, exploring the physical and mechanical properties of wood and their driving factors can help us to further understand the structure and function of terrestrial ecosystems, and thus provide valuable information for predicting the responses of terrestrial ecosystems to global change.…”
mentioning
confidence: 99%